Simulation and Modelling of Pre-emptive Priority CPU Scheduling Algorithm - Putra, Tri Dharma; Purnomo, Rakhmat (Sinkron : jurnal dan penelitian teknik informatika, 2024)
A model is a representation of an idea, thing or object in a simplified form. Model contains information about a system that is created with the aim of studying the actual system. Simulation is an imitation of system using a computer model. In this journal simulation is done by using OS-SIM, an operating system simulator. Process scheduling in an important part in operating systems. Several scheduling algorithms exist in the field. Shortest job first, round robin, first come first serve, priority and all of their variants. In this journal discussion about pre-emptive priority scheduling algorithm is presented thoroughly. Pre-emptive priority scheduling algorithm is an algorithm based on priority. The higher the number of the priority, the higher the priority. Five processes are available and given. Each with burst time, priority and different arrival times. Simulation and modelling with OS-SIM are discussed to understand this algorithm more easily. Some statistics numbers in the system are calculated automatically by the OS-SIM. Some screen shot pictures of the simulator are given to describe the model. It is concluded that for these processes the average turnaround time is 42/5 = 8.4 ms and for average waiting time is 28/5=5.6 ms and the total burst time is 14 ms.